2012
DOI: 10.1038/bmt.2012.43
|View full text |Cite
|
Sign up to set email alerts
|

Early evaluation of immune reconstitution following allogeneic CD3/CD19-depleted grafts from alternative donors in childhood acute leukemia

Abstract: Graft engineering procedures for hematopoietic SCT (HSCT) may improve the chance of success in matched unrelated donor (MUD) and haploidentical donor transplantations. Successful donor immune reconstitution is important to mediate GVL effects in reduced-intensity conditioning (RIC) HSCT. We prospectively investigated early immune reconstitution and clinical outcome in 30 CD3/CD19-depleted MUD (n ¼ 15) or HP (n ¼ 15) HSCTs for high-risk childhood leukemia using a fludarabine-based RIC without serotherapy. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 39 publications
5
37
0
1
Order By: Relevance
“…The NK cell isolation procedure was performed as described previously [25]. The following fluorochrome-labeled monoclonal antibodies (mAbs) against human antigens were obtained from Becton Dickinson: CD3 phycoerythrin (PE)-Cy7, CD158b1 fluorescein isothiocyanate (FITC), CD20-PE, CD45-FITC, CD69-FITC, NKG2D-alllophycocyanin (APC), CD45RA-PE-Cy5, CD127-APC, CD27-APC and CCR7-PE.…”
Section: Flow Cytometric Analysis and Tumor Immunohistochemical Analysismentioning
confidence: 99%
“…The NK cell isolation procedure was performed as described previously [25]. The following fluorochrome-labeled monoclonal antibodies (mAbs) against human antigens were obtained from Becton Dickinson: CD3 phycoerythrin (PE)-Cy7, CD158b1 fluorescein isothiocyanate (FITC), CD20-PE, CD45-FITC, CD69-FITC, NKG2D-alllophycocyanin (APC), CD45RA-PE-Cy5, CD127-APC, CD27-APC and CCR7-PE.…”
Section: Flow Cytometric Analysis and Tumor Immunohistochemical Analysismentioning
confidence: 99%
“…Phenotyping of natural killer (NK) cells, T lymphocytes, T lymphocyte subsets, B lymphocytes, NKT lymphocytes and dendritic cells (DCs) was performed on fresh samples of whole blood by multiparametric flow cytometry as previously described. 7 The following fluorochrome-labeled monoclonal Abs against human Ags were obtained from Becton Dickinson (San Jose, CA, USA): CD3 PE-Cy7, CD20-PE, CD45-FITC, lineage-FITC, HLADR-APC-Cy7, CD11c-PECy5, CD45RA-PE-Cy5 and CCR7-PE. Fluorochrome-labeled monoclonal Abs against CD19-PE, CD56-APC and CD25-PE were obtained from Beckman Coulter (Fullerton, CA, USA).…”
Section: Gvhd Prophylaxis and Supportive Carementioning
confidence: 99%
“…[10][11][12][13][14] Although all of our patients received GVHD prophylaxis with calcineurin inhibitors and mycophenolate mofetil, the incidences of severe acute and chronic GVHD were acceptable for our partial depletion of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports on HHCT using CD3-depleted grafts in pediatric patients. 2,[10][11][12][13][14] The Tübingen group reported their experience with CD3/19-depleted HHCT using reduced-intensity conditioning in 38 pediatric patients. 2 The authors reported a primary engraftment rate of 83%, with GR occurring in 17% of patients.…”
Section: Discussionmentioning
confidence: 99%